2017
DOI: 10.1111/joa.12631
|View full text |Cite
|
Sign up to set email alerts
|

Statistical shape modelling of hip and lumbar spine morphology and their relationship in the MRC National Survey of Health and Development

Abstract: The anatomical shape of bones and joints is important for their proper function but quantifying this, and detecting pathological variations, is difficult to do. Numerical descriptions would also enable correlations between joint shapes to be explored. Statistical shape modelling (SSM) is a method of image analysis employing pattern recognition statistics to describe and quantify such shapes from images; it uses principal components analysis to generate modes of variation describing each image in terms of a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 52 publications
(119 reference statements)
1
49
1
Order By: Relevance
“…Although osteoporosis was prevalent at other sites in this cohort, there was no evidence of hip osteoporosis in individuals included in this study (minimum Z ‐score −2.4) and few fractures; therefore, associations between walking age, hip shape, and fractures could not be explored. There was no effect of adjustment for hip BMD on associations between walking age and hip shape, although only weak associations between hip BMD and hip mode scores in this cohort have been reported . In addition, previous studies have shown that hip shape modes are predictive of hip fracture independent of BMD .…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…Although osteoporosis was prevalent at other sites in this cohort, there was no evidence of hip osteoporosis in individuals included in this study (minimum Z ‐score −2.4) and few fractures; therefore, associations between walking age, hip shape, and fractures could not be explored. There was no effect of adjustment for hip BMD on associations between walking age and hip shape, although only weak associations between hip BMD and hip mode scores in this cohort have been reported . In addition, previous studies have shown that hip shape modes are predictive of hip fracture independent of BMD .…”
Section: Discussioncontrasting
confidence: 48%
“…Three images were excluded because of extreme internal rotation of the femur, evidenced by femoral neck foreshortening, leaving 1633 images to build the hip SSM. SSM of hip images in this cohort has been described in detail previously . Briefly, a template of 68 points for the hip was placed around the area of interest in each image using Shape software (University of Aberdeen, Scotland).…”
Section: Participants and Methodsmentioning
confidence: 99%
See 3 more Smart Citations